2002
DOI: 10.1007/s00520-002-0346-3
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal infection in cancer patients treated with high-dose chemotherapy

Abstract: The infected and inflamed periodontium can act as a focus for systemic infection in neutropenic cancer patients. The incidence of these oral infections is unknown, but probably underestimated. Periodontal infections can easily be overlooked, primarily because symptoms of gingival inflammation may be minimal and the infection may be located in deeper parts of the periodontium. Assessment of a patient's periodontal condition before the onset of profound neutropenia is critical to the diagnosis and the management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 44 publications
(63 reference statements)
0
59
0
6
Order By: Relevance
“…Generally, periodontitis is diagnosed by measuring pocket depths and loss of attachment using a periodontal probe supplemented by radiographs [10]. The radiographic and gingival appearances in this case are shown in Fig.…”
Section: Clinical Oral Findings On First Visitmentioning
confidence: 99%
See 4 more Smart Citations
“…Generally, periodontitis is diagnosed by measuring pocket depths and loss of attachment using a periodontal probe supplemented by radiographs [10]. The radiographic and gingival appearances in this case are shown in Fig.…”
Section: Clinical Oral Findings On First Visitmentioning
confidence: 99%
“…However, the relative contributions of gingivitis and periodontitis to systemic infection in neutropenic cancer patients are largely unknown [10]. The incidence of so-called acute periodontal infections in previous studies showed significant disparity [10].…”
Section: Number Of Days Of Febrile Neutropenia In Each Chemotherapy Amentioning
confidence: 99%
See 3 more Smart Citations